Spatial diffusion of mobile telephony in Hungary - Tiner, Tibor (Hungarian Geographical Bulletin, 2010)
This article deals with the role of mobile telephony within the information society in general, the conditions of its use and the spatial characteristics and spatial features of its diffusion in different types of Hungarian sett lements. The introductory part of the paper gives a short survey about the most important features of wirelessness, as a technological basis of mobiltelephony. The following part of the study outlines some impacts of mobile telephony on the economy and the public sphere showing the main spatial trends observed nowadays in mobile communications development. The third part of the article makes a comparison between Hungarian sett lements (small towns) of a developed region (the Budapest agglomeration zone) and of less-favoured rural regions of South West Hungary evaluating the reasons for considerable differences.